Preventing Diabetic Foot Complications: The Essential Role of Nurses in Early Detection and Evidence-Based Care - Dewi Prabawati; Elise Eka; Riski Retnaningsih (AMK : Abdi Masyarakat UIKA, 2026)
Diabetic foot complications are common complications of diabetes mellitus that can lead to ulcers, infections, amputations, reduced quality of life, and increased healthcare costs. Nurses play an important role in the early detection and prevention of these complications through evidence-based care. However, knowledge and skills related to diabetic foot screening and foot care still need to be strengthened. This community service program aimed to improve nurses’ competencies in the early detection and prevention of diabetic foot complications. The activity was conducted face-to-face at a private hospital, South Tangerang and involved 27 nurses from various clinical units. The program consisted of four sessions covering concepts of diabetes mellitus; diabetic foot screening and early detection; followed by an evaluation. Participants’ knowledge was assessed using a diabetic foot care questionnaire. The results showed that 85.2% of participants had a high level of knowledge after attending the program. Participants also demonstrated a better understanding of foot screening, ulcer prevention, and proper foot care practices. This program effectively improved nurses’ knowledge and may support efforts to prevent diabetic foot complications among patients with diabetes mellitus.